PENGARUH MOTIVASI BERPRESTASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI NEGERI SIPIL (PNS) - Susi Budiwati (Jurnal Tata Kelola Pendidikan, 2021)
This research aims to obtain overview an effect of achievement motivation on the productivity of government employe in the center for teacher and education personel development of mechanical and industrial engineering Bandung. This research uses descriptive method with quantitative approach. Data collection techniques using a closed questionnaire that was distributed to 66 government employe in PPPPTK BMTI Bandung as a research sample. The hypothesis proposed is the exixtence of a positive and significant effect between achievement motivation (X) on the productivity (Y) of government employe in PPPPTK BMTI Bandung. Weight Means Score (WMS) calculation results show that achievement motivation scores of 3,36 are included in the very high category and work productivity get a value of 3,46 included in the very high category. To test the research hypothesis several steps were carried out, namely correlation analysis between variabels using Pearson Product Moment obtained a result of 0,821 wich showed the correlation of reliation between the 2 variables was at the level of a positive and very strong relation. Then the significance test using t test result obtained thitung 11,495ttabel 1,997 means that there is a significant relation between the X variabel and the Y variable. The coefficient of determination test result obtained that the variable X affects the Y variable by 67,4% and the rest is influensced by other variables not examined in this research, while in the regression analysis obtained by (Y ) ̂= 16,585 + 0,821X equation this means that if there is an increase of one in the Y variable it will be followed by an increase of 0,821 in the X variable. The conclusion of this study is that there is a significant and positive influence between achievement motivation on the productivity of government employe in the center for teacher and education personel development of mechanical and industrial engineering Bandung.